Lung function decline before and after treatment of World Trade Center associated obstructive airways disease with inhaled corticosteroids and long‐acting beta agonists. Issue 10 (13th July 2021) - Goldfarb, David G.; Putman, Barbara; Lahousse, Lies; Zeig‐Owens, Rachel; Vaeth, Brandon M.; Schwartz, Theresa; Hall, Charles B.; Prezant, David J.; Weiden, Michael D.
Abstract: Background: Greater than average loss of one‐second forced expiratory volume (FEV1 ) is a risk factor for asthma, chronic obstructive pulmonary disease (COPD), and asthma/COPD overlap syndrome in World Trade Center (WTC)‐exposed firefighters. Inhaled corticosteroids and long‐acting beta agonists (ICS/LABA) are used to treat obstructive airways disease but their impact on FEV1 ‐trajectory in this population is unknown. Methods: The study population included WTC‐exposed male firefighters who were treated with ICS/LABA for 2 years or longer (with initiation before 2015), had at least two FEV1 measurements before ICS/LABA initiation and two FEV1 measurements posttreatment between September 11, 2001 and September 10, 2019. Linear mixed‐effects models were used to estimate FEV1 ‐slope pre‐ and post‐treatment. Results: During follow‐up, 1023 WTC‐exposed firefighters were treated with ICS/LABA for 2 years or longer. When comparing intervals 6 years before and 6 years after treatment, participants had an 18.7 ml/year (95% confidence interval [CI]: 11.3–26.1) improvement in FEV1 ‐slope after adjustment for baseline FEV1, race, height, WTC exposure, weight change, blood eosinophil concentration, and smoking status. After stratification by median date of ICS/LABA initiation (January 14, 2010), earlier ICS/LABA‐initiators had a 32.5 ml/year (95% CI: 19.5–45.5) improvement in slope but later ICS/LABA‐initiators had a nonsignificant FEV1 ‐slope improvement (7.9 ml/year, 95% CI: −0.5 to 17.2). Conclusions: WTC‐exposed firefighters treated with ICS/LABA had improved FEV1 slope after initiation, particularly among those who started earlier. Treatment was, however, not associated with FEV1 ‐slope improvement if started after the median initiation date (1/14/2010), likely because onset of disease began before treatment initiation. Research on alternative treatments is needed for patients with greater than average FEV1 ‐decline who have not responded to ICS/LABA.